2020
DOI: 10.1596/1813-9450-9230
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare Effects of Mobile Broadband Internet: Evidence from Nigeria

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 11 publications
5
34
2
Order By: Relevance
“…3G coverage does not have a significant impact on overall employment. These findings are consistent with other studies (e.g., Bahia et al 2020;Hjort and Poulsen 2019) showing similar results: that access to the Internet translates into increased employment in wage or higher-skilled jobs. Our finding draws attention to the potential role that digital technologies can play in improving labor outcomes -and particularly, employment in "better" jobs.…”
Section: ) 19supporting
confidence: 93%
See 3 more Smart Citations
“…3G coverage does not have a significant impact on overall employment. These findings are consistent with other studies (e.g., Bahia et al 2020;Hjort and Poulsen 2019) showing similar results: that access to the Internet translates into increased employment in wage or higher-skilled jobs. Our finding draws attention to the potential role that digital technologies can play in improving labor outcomes -and particularly, employment in "better" jobs.…”
Section: ) 19supporting
confidence: 93%
“…2 Recent evidence thus suggests that an expansion of fixed broadband Internet would enable more rapid job creation, more economic activity in Africa, and greater productivity and export growth among firms (Hjort and Poulsen 2019). New research also shows that the rollout of mobile broadband Internet has increased household consumption and reduced moderate and extreme poverty in Nigeria (Bahia et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Broad access to information and communication technology (ICT) has great potential for poverty reduction and inclusive growth in developing countries, where ICT adoption is growing rapidly (World Bank 2016). Recent studies have shown that the expansion of broadband through fiber optics and mobile internet produces substantial benefits in household income and consumption, employment and productivity, and helps lift people out of poverty (see Bahia et al 2020 on Nigeria, which accounts for the largest ICT market in Africa; Masaki, Granguillhome Ochoa, and Rodríguez-Castelán 2020 for Senegal; and Hjort and Poulsen 2019 on Africa). However, that ICT markets in most countries in Africa rank among the most concentrated in the world has limited the potential for equity and efficiency gains in digital technology adoption among households and firms across the region.…”
Section: Introductionmentioning
confidence: 99%